TEACHING METHODOLOGY IN THE HIGHER EDUCATION SYSTEM (International conference on multidisciplinary science, 2026)
The evolution of teaching methodologies in higher education reflects a fundamental paradigm shift from traditional transmission-based models toward dynamic, student-centered, and technology-enhanced approaches. This article synthesizes contemporary research to examine the theoretical foundations, practical implementations, effectiveness, and challenges of modern pedagogical strategies. Particular attention is given to flipped learning, problem-based learning, collaborative methodologies, blended and hybrid formats, gamification, and the integration of educational technologies. The discussion highlights how these methods influence cognitive, metacognitive, and socio-emotional learning outcomes, while also analyzing the critical mediating roles of faculty pedagogical expertise, institutional culture, leadership style, and contextual constraints. The article argues that sustainable improvement in higher education teaching requires moving beyond isolated methodological innovations toward coherent, evidence-informed, institutionally supported hybrid pedagogical ecosystems.